Optimasi Sistem Boiler dengan Variasi Pengaturan Temperatur - Muhammad Nuriyadi; Faldian Faldian (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
In the air conditioning system, hot water boilers are used for the purpose of room heating and reheating processes. In tropical countries, the function of space heating is carried out for process rooms, while the function of hot water for the reheating process is widely used. In this case, the hot water produced by the boiler is used for the reheating process in the Air Handling Unit (AHU). In the process of energy conservation, to reduce the use of energy in boiler systems, especially in air conditioning systems to make it more efficient, it is necessary to take steps to save energy along with the evaluation process of energy use, identify opportunities for energy savings, and recommendations for increasing efficiency in energy use. This study aims to evaluate the boiler system to ensure that the design of the boiler system can work and produce planned air conditioning, as well as assess energy-saving opportunities. Boiler system performance testing is done by setting various variations in the temperature of the hot water output, which is 50 oC, 60 oC, 70 oC, and 80 oC. Testing is done by looking at how long it takes to reach the set temperature. After that, each increase in temperature is calculated as the resulting efficiency. The average combustion energy consumption in the boiler is 50.23 kJ/s. The average energy transferred to hot water is 39.82 kJ/s. Overall the highest efficiency of the boiler system is achieved at a set temperature of 80 oC, which is 71.5 %.